PELATIHAN BUDIDAYA SORGUM UNTUK PAKAN TERNAK SAPI - Hanisah; Dolly Sojuangan Siregar; Muhammad Syahril (LPPM dan PM Universitas Samudra, 2020)
Sorghum plants are used as raw materials for various industries including animal feed. In Indonesia, the use of sorghum plants is more directed as animal feed. With the ability to grow in various places, sorghum plants (Sorghum bicolor L.) have the opportunity to be developed on nonproductive land such as in the village of Sarah Teubee. Sara Teubee village with an area of ​​32 ha of rain-fed rice fields will be potential to develop sorghum plants. In this case, the Faculty of Agriculture, Samudra University has a moral responsibility to overcome these problems as well as efforts to develop sorghum plants, especially in the region of East Aceh, Langsa City and Aceh Tamiang. The effort to introduce the sorghum plant is done through community service (PKM) funded by LPPM and PM Universitas Samudra. Community service activities have been carried out in Sara Teubee, Rantau Selamat District, East Aceh District. Community service activities include planting location surveys, Focus Group Discussion (FGD), sorghum planting training, and how to make cattle feed from sorghum plants. The output of this study is the farmer group as an indicator of understanding about sorghum cultivation techniques and using sorghum plants as animal feed. In addition, other outcomes of this service are publications in print media and scientific journals of service.